The orally available multikinase inhibitor regorafenib (BAY 73-4506) in multiple myeloma - Breitkreutz, Iris; Figueroa Vazquez, Vianihuini; Raab, Marc-Steffen (Annals of hematology, 2018)
A promising approach to the treatment of multiple myeloma (MM) involves agents that target not only the myeloma cells directly, but also the tumor microenvironment which promotes tumor cell growth, angiogenesis, and MM bone disease. Here we investigate the orally available multikinase inhibitor, regorafenib (BAY 73-4506), for its therapeutic efficacy in MM. Regorafenib is a potent inhibitor of angiogenic (VEGFR 1-3, PDGFR-b) as well as oncogenic (c-KIT, RET, FGFR, Raf) kinases. We show that regorafenib induces apoptosis in all MM cell lines at below clinically achievable concentrations. Regorafenib overcomes the growth advantage conferred by a stroma cell MM and an endothelial cell MM, co-culture systems, and abrogates growth factor-stimulated MEK, ERK, and AKT phosphorylation at nanomolar to micromolar concentrations. Moreover, it inhibits endothelial cell growth and tubule formation, abrogates both VEGF secretion and VEGF-induced MM cell migration, inhibits osteoclastogenesis, and shows synergistic cytotoxicity with dexamethasone, the immunomodulatory drug pomalidomide, and the p110δ inhibitor idelalisib. Most importantly, regorafenib significantly delays tumor growth in a xenograft mouse model of human MM. These results provide the rationale for further clinical evaluation of regorafenib, alone and in combination, in the treatment of MM.